Long Noncoding RNA: Shining Stars in the Immune Microenvironment of Gastric Cancer - Xiao, Xian; Cheng, Wen; Zhang, Guixing; Wang, Chaoran; Sun, Binxu; Zha, Chunyuan; Kong, Fanming; Jia, Yingjie (Frontiers in Oncology, 2022)
Gastric cancer (GC) is a kind of malignant tumor disease which seriously threatens human health. GC immune microenvironment (TIME) is a very complex tumor microenvironment, mainly composed of infiltrating immune cells, extracellular matrix, tumor-associated fibroblasts, cytokines and chemokines, which play a key role in inhibiting or promoting tumor development and affecting tumor prognosis. Long non-coding RNA (lncRNA) is a kind of non-coding RNA whose transcript length is more than 200 nucleotides. LncRNAs are expressed in various infiltrating immune cells in TIME and involved in innate and adaptive immune regulation, which is closely related to immune escape, migration and invasion of tumor cells. LncRNA-targeted therapeutic effect prediction for GC immunotherapy opens up a new perspective for clinical research on GC.